Lipodystrophy induced by combination antiretroviral therapy in HIV/AIDS patients: A Belgrade cohort study - Dragović, Gordana; Danilović, Dragana; Dimić, Aleksandra; Jevtović, Djordje (Vojnosanitetski pregled, 2014)
Background/Aim. Highly active antiretroviral therapy (HAART) has led to dramatic reductions in mortality and morbidity of HIV/AIDS-patients. Lipodystrophy, a syndrome including peripheral fat wasting and central obesity, is well-documented side effect of HAART. The aim of this study was to evaluate the incidence of lipodystrophy, and to determine its risk ratios in a HIV/AIDS-cohort. Methods. This cross-sectional study included all the antiretroviral-naive HIV/AIDS patients commencing HAART from October 1, 2001 to October 1, 2010, at the HIV/AIDS Center, Institute of Infectious and Tropical Diseases, Belgrade, Serbia. Univariate and stepwise multivariate logistic regression analyses were used to determine the odds ratios (OR) with the confidence interval (CI) of 95%, in order to establish the relative risk for lipodystrophy. The Kaplan-Meier-method was used to determine the probability of development lipodystrophy over time. All statistical analyses were performed using SPSS software version using 0.05 as a p-treshold for the significance. Results. This study included 840 HIV/AIDS patients, 608 women and 232 men, followed for 5.6 ± 2.8 years. The prevalence of lipodystrophy was 69.2%. Univariate and stepwise multivariate regression analysis identified that the female gender, hepatitis C coinfection, AIDS diagnosis prior to HAART initiation, nucleoside-reverse-transcriptase-inhibitors and protease-inhibitors based regimens had a high risk for developing lipodystrophy in HIV/AIDS-patients (OR = 1.6, 95% CI = 1.1–3.49, p = 0.04; OR = 3.31, 95% CI = 1.3–6.8, p < 0.01; OR = 3.7, 95% CI = 1.7–6.1, p < 0.01; OR = 2.1, 95% CI = 1.7–3.3, p < 0.01; OR = 6.1, 95% CI = 4.1–9.7, p < 0.01, respectively). Conclusion. Despite much greater life expectancy of HIV/AIDS-patients, treatment-related toxicities still remain a major concern. Monitoring of lipodystrophy, as side effect of HAART, is particularly important.